Quality Drivers of Local Government Financial Reports: Examamining the Moderating Role of Information Technology in Bintan Regency - Giantoro Rudiman; Chablullah Wibisono; Bambang Satriawan; R.A Widyanti Diah Lestari; Adi Budiarso (Jurnal Akuntansi, 2025)
The assessment results of government financial statements in Indonesia remain a concern for academics, practitioners, and researchers. Although the WTP opinion is the highest rating from the Indonesian Audit Board on Local Government Financial Statements, problems persist, such as errors in presentation that do not comply with SAP, weak internal control systems (SPI), and recurring findings despite follow-up actions outlined in the TLRHP report. The achievement of WTP reflects the quality of financial reports prepared by central and regional governments, yet challenges remain in ensuring consistency and compliance. This study aims to examine the influence of SAP implementation, human resource quality, and SPIP on the quality of local government financial reports, with information technology as a moderating variable, focusing on Bintan Regency. Using a quantitative method supported by descriptive analysis and data triangulation, data were obtained through questionnaires and interviews with 140 respondents from 39 regional agencies. Smart PLS Version 4.0 software was applied for analysis. The results show that SAP, SPIP, and information technology positively and significantly affect the quality of LKPD in Bintan Regency. In contrast, human resource quality has a negative and insignificant effect. Moreover, information technology moderates the effect of SAP on LKPD quality but does not moderate the influence of human resource quality and SPIP.